Analysis on the Preparation of International Standard Implementation to Indonesia Automotive Industry Expected Performance Facing ASEAN Economic Community 2015 - Muhammad Ikhsan; Nila K. Hidayat; Linus Pasasa (Jurnal Manajemen dan Bisnis Indonesia, 2014)
This is largely due to the substantial range of networking and interconnectivity brought on by the positive surge of development in global trade that enables companies to expand their business overseas and reach out to more than just domestic markets scene. The ASEAN Economic Community 2015 is a challenge to make a single barrier free market all through of the 10 (ten) member countries, devoid of barriers its services, capital, and allowing goods, and skilled labor to move freely across borders. ASEAN Member States are agreed to implementing UNECE Wp. 29 for to be a basis harmonization automotive technical regulation in ASEAN region. The purpose of this thesis is to measure a correlation between UNECE International Automotive Standard and The Indonesia Automotive Industry (expected) performance. As a result it has been concluded that correlations between UNECE International Automotive Standard and Indonesia Automotive Industry performance does exists. Implementing UNECE International Standard bring technologies, economic and social benefits into the country and the manufacturing and it will helps to contribute an improvement in Automotive Industry in Indonesia. Process documentation and control is the major influence towards improving the performance of Automotive Industry in Indonesia and Supplier Related Benefits is the factor that gives a significant influence for improvement Indonesia Automotive Industry performance. Keywords : AEC 2015, UNECE International Automotive Standard, ASEAN MRA, Indonesia Automotive Industry.